Ultrasonic transducers from thermal sprayed lead-free piezoelectric ceramic coatings for in-situ structural monitoring for pipelines. (12th June 2019) - Guo, Shifeng; Zhang, Lei; Chen, Shuting; Tan, Chee Kiang Ivan; Yao, Kui
Abstract: Direct-write ultrasonic transducers comprised of lead-free ceramic coatings were designed and in situ fabricated by thermal spray process onto stainless steel pipe structures. The experimental measurements and simulation analyses showed that both external and internal defects on the pipe structures could be effectively detected with the ultrasonic Lamb waves propagating along the axial direction, which were excited and detected using the direct-write ultrasonic transducers. The results suggested that the implementation of the direct-write ultrasonic transducers made of the lead-free piezoelectric ceramic coating by thermal spray method is promising for realizing structural health monitoring for pipeline structures with improved consistency and reliability. It is also an important step moving toward smart pipelines with real-time self-diagnostic function.